Impact of Dienogest Alone or in Combination with Ethinylestradiol on the Quality of Life of Women with Endometriosis: A Prospective Cohort Study - Canday, Mujde; Salman, Suleyman (Gynecology Obstetrics & Reproductive Medicine, 2023)
OBJECTIVE: We aim to compare the effectiveness of oral contraceptives and dienogest, primarily by considering the quality of life scale. We also aim to compare the Cancer Antigen-125 and Anti-mullerian Hormone values. STUDY DESIGN: Gynecological examination findings evaluated based on ESHRE and ASRM Guideline criteria are compatible with endometriosis, or a previous surgery pathology result is consistent with endometriosis, and patients whose imaging report was compatible with endometriosis were selected. Among the patients who were recommended medical treatment, patients selected as Dionegest 2mg+Ethinylestradiol 0.03 mg (Dienelle) treatment were considered Group 1, and patients deemed suitable for treatment with treatment 2mg Dionegest (Visanne) were considered Group 2. Pre-treatment Cancer Antigen-125/Anti-mullerian Hormone values and SF-36 were recorded. RESULTS: There was no significant difference between drug groups in terms of education status, body mass index, family history, smoking, alcohol consumption, age, age at menarche, menstruation pattern, duration of menstruation, infertility, gestational status, job loss due to pain complaints, operation, and MRI findings (p>0.05). There was no significant difference between the drug groups regarding the quality of life before and after treatment (p>0.05). There was no significant difference between drug groups regarding endometrioma size, Cancer Antigen-125, and anti-mullerian hormone findings (p>0.05). CONCLUSION: Evaluating our data, the efficacy and success of the two treatment protocols were the same. It seems more logical to prefer cost-effective oral contraceptive treatments with a low side-effect profile than high-cost Dionegest. Following the guidelines accepted step therapy in treating mild or moderate endometriosis, cyclic oral contraceptives may be recommended as first-line therapy.